Pretreatment in dehydrated candied jackfruit (Artocarpus integra Linn.) - Lukban, Ma. Cecilia G.; De Leon, Sonia Y. (1983.)
The purpose of this study was to find the best pre-drying treatment for dehydrated candied jackfruit. To do so, the effects of blanching and/or sulfiting on the organoleptic and storage qualities were determined. Statistical analyses for the sensory evaluation proved that the dehydrated candied jackfruit bulbs which were immersed in 0.1% sodium metabisulfite prior to dehydration and those which were steam blanched for 3 minutes then immersed 0/1% sodium metabisulfite did not differ significantly. This is in terms of appearance, color, flavor, texture and general acceptability. However, the blanched/sulfited sample was the most preferred product among the control, the blanched, and the sulfited sample. Sorption isotherm were constructed for the dehydrated candied jackfruit subjected to different pre-drying treatments. The resulting curves were all sigmoidal in shape. The region where the samples exhibited maximum stability was identified at RH range 8.0% to 70.4%.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Jackfruit, Candied